Analisis Penerapan Sistem Pengendalian Internal Atas Akuntabilitas Pengelolaan Keuangan Desa di Desa Sidorukun Kecamatan Randangan - Septian Sulistiawan; Mattoasi; Lukman Pakaya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Septian Sulistiawan, 2024. “Analysis of the Implementation of internal Control System on Accountability of Village Financial Management in Sidorukun Village, Randangan Subdistrict”. Accounting Study Program, Department of Accounting, Faculty of Economics, Universitas Negeri Gorontalo. The Principal Supervisor: Mattoasi, S.Pd,.SE M.Si, Ph.D The Co-supervisor: Lukman Pakaya, S.Pd., MSA. This research aimed to answer how the implementation of the internal control system on accountability related to village financial management in the governmentof Sidorukun Village, Randangan Subdistrict, Pohuwato Regency. This study was qualitative research using a descriptive analysis method. The research data sources used primary and secondary data was obtained from documentation of the internal control system on the accountability of village financial management in Sidorukun Village was quite good and structured based on applicable regulations. However, in village financial management, it was found that the management of village wealth and assets was not accountable, and there was a lack of qualified human resources due to educational issues. This indicates that the internal control system in maximizing village financial management is optimal in its implementation, although there is a lack of knowledge among village officials in terms of village financial management, requiring continuous assistancefrom local government offcials.